Age‐related changes in blood pressure and heart rates of patients with Parkinson's disease - Kazumasa Shindo; Yuto Morishima; Yumi Suwa; Toko Fukao; Takafumi Kurita; Akane Satake; Mai Tsuchiya; Yuta Ichinose; Takanori Hata; Kishin Koh; Takamura Nagasaka; Yoshihisa Takiyama (The Journal of Clinical Hypertension, 2021)
Abstract This study evaluated yearly changes in systolic blood pressure (SBP), diastolic blood pressure (DBP), and heart rates (HR) for patients with Parkinson's disease (PD). Data were collected for the last 10 years from medical records of 28 PD patients and 30 non‐PD patients with other neurological disorders. Age‐related changes in each group were analyzed by year using mean values of SBP, DBP, and HR obtained at their bi‐monthly visits. In results, PD patients had a gradual decrease in SBP with longer disease duration, and mean SBP significantly decreased from Year 7–11 compared to the mean values for Year 1 (p < .001 or p < .01). In non‐PD patients, mean SBP significantly increased from Year 4–11 compared to the mean values for Year 1 (p < .001 or p < .01). This is the first study to report age‐related changes of BP in individual patients with PD over 10 years.